Coordinative integration of amorphous nickel-imidazole framework with graphitic carbon nitride for enhanced photocatalytic hydrogen production. (August 2022) - Rajan, Aswathy; Neppolian, B.
Highlights: Synthesis of a new nickel based imidazole framework (Ni-MOF) and its amorphous counterpart (aNi-MOF) via a simple solvothermal route. The optoelectronic studies on Ni-MOF and aNi-MOF confirmed their potential applicability for photocatalytic hydrogen production. Structural reconstruction of aNi-MOF with different g-C3 N4 precursors (urea, thiourea and melamine) to extend the photocatalytic absorption. The aNi-MOF integrated g-C3 N4 shows ∼2200 folds enhanced photocatalytic hydrogen production than pristine photocatalyst. Proposed a mechanism for photocatalytic hydrogen production by g-C3 N4 /aNi-MOF photocatalyst. Abstract: Herein, a new nickel metal-organic framework (Ni-MOF) was integrated with graphitic carbon nitride (g-C3 N4 ) (prepared by polycondensation of different precursors, i.e., urea, thiourea and melamine) using the solvothermal method and used for the photocatalytic hydrogen production. Notably, crystalline Ni-MOF was unable to bond with g-C3 N4 due to completely coordinated nickel sites in Ni-MOF, but amorphous Ni-MOF (aNi-MOF) successfully bonded with g-C3 N4 owing to its uncoordinated nickel sites. The aNi-MOF incorporated with g-C3 N4 (prepared by urea) exhibited hydrogen production of 2272.6 μmol g −1 h − 1 which was ∼450, 4 and 7 times higher than aNi-MOF, thiourea and melamine derived g-C3 N4 integrated with aNi-MOF, respectively. The substantial increment in photocatalytic activity can be attributed to the synergistic structural reconstruction of g-C3 N4 /aNi-MOF in accordance with varying dangling amine groups, surface area and porosity offered by different precursors in formation of g-C3 N4 . Remarkably, the proposed work is the first report on the photocatalytic hydrogen production by an amorphous metal-organic framework and also an imidazole-based nickel framework. Thus, this work provides insight into the designing amorphous MOF- extended polymer heterostructure and will open up a new avenue to their catalytic performances. Graphical abstract: Image, graphical abstract